(untitled) (Training and Practice : Journal of Educational Sciences, 2008)
Urbanization, sedentary mode of life and force of pressure of performance features today’s society as a consequence of 10-14 working hours a day, which is typical in Central and Eastern European countries, stress, and intensified life style. Getting stuck in the daily routine, fast food and media-addict population of the 21st century has to cope with several diseases. Considering these illnesses regular physical training, especially swimming can be mentioned as one of the most significant tools of prevention or rehabilitation. Children and adults go to swimming pool with the aim of recreation and rehabilitation rather than pursuing swimming competitively. Parents want to bring up healthy, apt-to-act generations, only a small percentage expects their children to take part in competitive sports with good results. Demands and requirements of society have changed in the last ten years, and this process involved a transformation in the aim and objective system of swimming. This tendency makes it necessary to introduce and define recreation swimming and adaptation swimming as new concepts. By presenting aim and objective system of adaptation physical education we make an attempt to describe the aims, objectives and definition of recreation swimming and adaptation swimming in this paper. We focus on factors that clearly show similarities and differences between recreation swimming and adaptation swimming. We consider it crucial if we want to take the first steps in promoting the renewal and improvement of the two above mentioned forms of swimming. As far as we are concerned it seems necessary that these two kinds of physical education meet the expectations of today’s changing society.